Cardiovascular evaluation after COVID-19 in 137 collegiate athletes: Results of an algorithm-guided screening - Hendrickson, B. S.; Stephens, R. E.; Chang, J. V.; Amburn, J. M.; Pierotti, L. L.; Johnson, J. L.; Hyden, J. C.; Johnson, J. N.; Philip. R. R. (Circulation, 2021)
Concerns for cardiovascular sequelae of coronavirus disease 2019 (COVID-19), including myocardial injury or myocarditis, brought about recommendations for evaluating athletes after infection with the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).1 Assessments that were based on symptoms, disease severity, and cardiovascular testing were refined to guide decision making and safe return to play in various groups.2 However, cardiac magnetic resonance (CMR) findings of myocarditis in athletes have ranged from as high as 15% (4 out of 26 athletes in one study) to as low as 1.4% (2 out of 145 athletes in another study), many of whom had no or only mild symptoms, have raised concerns around testing in this population.3,4 CMR is a recognized tool for diagnosing myocarditis yet is not generally recommended for athletes after COVID-19 without an elevated index of suspicion.2,5 Given limited data in competitive athletes after infection with SARS-CoV-2, we report our initial experience with an algorithm-guided screening of collegiate athletes and intermediate-term follow-up.